Human Umbilical Cord Mesenchymal Stem Cell–Based in vitro Model for Neurotoxicity Testing. Issue 4 (26th April 2022) - Coccini, Teresa; Spinillo, Arsenio; Roccio, Marianna; Lenta, Elisa; Valsecchi, Chiara; De Simone, Uliana
Abstract: Neurotoxicity (NT) testing for regulatory purposes is based on in vivo animal testing. There is general consensus, however, about the need for the development of alternative methodologies to allow researchers to more rapidly and cost effectively screen large numbers of chemicals for their potential to cause NT, or to investigate their mode of action. In vitro assays are considered an important source of information for making regulatory decisions, and human cell–based systems are recommended as one of the most relevant models in toxicity testing, to reduce uncertainty in the extrapolation of results from animal‐based models. Human neuronal models range from various neuroblastoma cell lines to stem cell–derived systems, including those derived from mesenchymal stem/stromal cells (hMSC). hMSCs exhibit numerous advantages, including the fact that they can be obtained in high yield from healthy human adult tissues, can be cultured with a minimal laboratory setup and without genetic manipulations, are able of continuous and repeated self‐renewal, are nontumorigenic, and can form large populations of stably differentiated cells representative of different tissues, including neuronal cells. hMSCs derived from human umbilical cord (hUC) in particular possess several prominent advantages, including a painless, non‐invasive, and ethically acceptable collection procedure, simple and convenient preparation, and high proliferation capacity. In addition, hMSCs can be efficiently differentiated into neuron‐like cells (hNLCs), which can then be used for the assessment of neuronal toxicity of potential neurotoxic compounds in humans. Here, we describe a step‐by‐step procedure to use hMSCs from the umbilical cord for in vitro neurotoxicity testing. First, we describe how to isolate, amplify, and store hMSCs derived from the umbilical cord. We then outline the steps to transdifferentiate these cells into hNLCs, and then use the hNLCs for neurotoxicity testing by employing multiple common cytotoxicity assays after treatment with test compounds. The approach follows the most updated guidance on using human cell–based systems. These protocols will allow investigators to implement an alternative system for obtaining primary NLCs of human origin, and support advancement in neurotoxicity research. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Isolation and maintenance of human mesenchymal stem/stromal cells (hMSCs) obtained from the umbilical cord lining membrane Basic Protocol 2 : Transdifferentiation of hMSCs into neuron‐like cells (hNLCs) and basic neurotoxicity assessment